3D visualization modeling of nonwoven fabrics from multi-focus images. Issue 3 (31st March 2022) - He, Yan; Deng, Na; Xin, Binjie; Liu, Lulu
Abstract: Nonwoven fabrics are composed of many fibers directly and including rich information in the longitudinal direction, so the general image processing technology cannot meet the needs of analysis of nonwovens. Therefore, the visualization of the three-dimensional microstructure of nonwoven fabrics is the key to the comprehensive analysis of nonwoven fabrics. To solve this problem, a micro-imaging system is designed and a 3 D visualization method based on marching cubes algorithm is proposed. Firstly, multi-focus image sequences covering the longitudinal information of nonwoven fabrics are captured in different focal planes. Secondly, the bottom-hat transform algorithm is used to correct the images' background. Thirdly, the fiber is filled and the noise outside the fiber is removed by morphology operation. Then the focused fiber is segmented to form a binary image sequence. Finally, the binarized images are processed by marching cubes algorithm and the 3 D visualization of nonwoven fabrics can be realized greatly.